Evaluation Model of Institutions Based on Scriven's Consumer-Oriented Approach to Improve the Quality of Digital Services for Students - Dian Pertiwi Josua; Nuridayanti; Riyadi; Soeprijanto; Aip Badrujaman (Jurusan Teknik Informatika dan Komputer, 2025)
This study aims to implement an institutional evaluation model based on Consumer-Oriented Scriven to improve the quality of digital services for students at the State University of Jakarta (UNJ). The available digital services are considered less than optimal by students, so an evaluation model is needed that focuses on user needs and satisfaction. This study uses a mixed approach with a case study method, with data collection through in-depth interviews, surveys, and direct observation. The quantitative survey used a Likert scale to measure student satisfaction with various aspects of digital services, such as academic information systems (73% satisfied), e-learning (68%), financial applications (65%), online registration (70%), and online help services (66%). The validity of the analysis instrument was tested through factors and expert assessments, while the reliability showed a Cronbach Alpha (α) value of 0.87 which is classified as very good. The results of the study indicate that this evaluation model is able to identify areas that need to be improved and encourage student participation in the service evaluation process. The application of the consumer-oriented Scriven evaluation model has been shown to make a significant contribution to improving the quality of digital services at UNJ which are more responsive and efficient.